OC-002 Increased participation in colorectal cancer screening during a pilot of faecal immunochemical test for haemoglobin (FIT) in england. (22nd June 2015) - Moss, S; Mathews, C; Day, T; Smith, S; Halloran, SP
Abstract : Introduction: The NHS Bowel Cancer Screening Programme (BCSP) in England has used a guaiac faecal occult blood test (gFOBt) since 2006. In April 2014 the BCSP commenced a six-month FIT Pilot study to assess the clinical, financial and organisational implications of adopting FIT. Method: Two regional BCSP Hubs (Southern and Midlands and North West) and associated Screening Centres participated in the pilot study. One in 28 invitees was offered FIT rather than gFOBt. 30, 000 FIT invitations provided adequate power for analysis of FIT uptake compared with gFOBt. The OC-SENSOR FIT system (Eiken Chemical Co. Ltd., Japan) was used with a cut-off for positivity of 20 µg haemoglobin [Hb]/g faeces (100 ng Hb/mL buffer). Results: 39, 460 subjects were sent a FIT and 1, 067, 120 a gFOBt during the pilot period (April–October 2014). Uptake of FIT was significantly higher than gFOBt (67.6% vs. 60.1%; OR 1.38). The increase in uptake was significantly greater for previous non-responders (FIT 26.6% vs. gFOBt 14.5%; OR 2.13), compared with subjects invited for the first time (61.4% vs 50.2%; OR 1.58) and those who had participated previously (91.0% vs 86.6%; OR 1.57). The increase in uptake was higher in males (FIT 65.5% vs. gFOBt 57.0%; OR 1.89) than females (69.6% vs. 63.2) and was apparent for all quintiles of deprivation. Of particular note is the increase in uptake with FIT compared with gFOBt in the most deprived and traditionally 'hard-to-reach' quintile (55.1% vs 46.9%; OR 1.39). Overall positivity was 7.8% with FIT (cut-off 20 µg Hb/g faeces) and 1.7% with gFOBt (OR 4.87). The increase in positivity was similar in males and females and in all deprivation quintiles, but increased with age. Significantly more colorectal cancers (CRC) (0.22% FIT vs. 0.10% gFOBt; OR 2.25) and advanced adenomas (1.56% vs. 0.30%; OR 5.21) were detected with FIT. The PPV for all neoplasms was significantly higher with FIT (54.7% vs. 50.5%; OR 1.18). At a cut-off of 150 µg Hb/g faeces (750 ng Hb/mL buffer), which yielded a positivity for FIT (1.8%) similar to gFOBt, FIT had a higher detection rate and PPV for advanced adenomas and all neoplasms. Conclusion: FIT significantly increased uptake of screening and provides an opportunity to adjust the faecal Hb concentration cut-off for positivity and thus the burden on colonoscopy resource. Further analysis will determine how the faecal Hb concentration measured by FIT could be incorporated into a multivariate risk score for CRC. Disclosure of interest: None Declared.